Halal Tourism Based Economy Development - Darsono, Cipto; Uyun, Muhammad; Isnaini, Muhammad (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
This article examines the economic development based on halal tourism in Lampung Province. Tourism is a sector that has a very significant impact on national income. The increase in tourist visitors from year to year is also welcomed by the government in developing halal tourism along with increasing public awareness of halal products.Lampung province as one of the areas that continues to increase the number of tourists coming each year also needs to develop halal tourism, the implementation of halal tourism in Lampung province is expected to increase the economic growth of the community. The research uses qualitative methods,with data sources in the form of interviews, field observations and related documents. The result of this study indicate that the implementation of halal tourism can be realized because of four aspects, namely the system used based on Islamic sharia principles, the availability of halal products, the availability of halal facilities, and the comfort and safety of tourist. The implementation of the four aspects of halal tourism will be able to increase the economic growth of the community in Lampung Province amid increasing public awareness of halal products which are considered clearer and more reliable, not only by Muslims but also by non-Muslims.